Array comparative genomic hybridization and fetal congenital heart defects: a systematic review and meta‐analysis. (2nd January 2015) - Jansen, F. A. R.; Blumenfeld, Y. J.; Fisher, A.; Cobben, J. M.; Odibo, A. O.; Borrell, A.; Haak, M. C.
ABSTRACT: Objective: Array comparative genomic hybridization (aCGH) is a molecular cytogenetic technique that is able to detect the presence of copy number variants (CNVs) within the genome. The detection rate of imbalances by aCGH compared to standard karyotyping and 22q11 microdeletion analysis by fluorescence in‐situ hybridization (FISH), in the setting of prenatally‐diagnosed cardiac malformations, has been reported in several studies. The objective of our study was to perform a systematic literature review and meta‐analysis to document the additional diagnostic gain of using aCGH in cases of congenital heart disease (CHD) diagnosed by prenatal ultrasound examination, with the aim of assisting clinicians to determine whether aCGH analysis is warranted when an ultrasonographic diagnosis of CHD is made, and to guide counseling in this setting. Methods: Articles in PubMed, EMBASE and Web of Science databases from January 2007 to September 2014 describing CNVs in prenatal cases of CHD were included. Search terms were: 'array comparative genomic hybridization', 'copy number variants' and 'fetal congenital heart defects'. Articles regarding karyotyping or 22q11 deletion only were excluded. Results: Thirteen publications (including 1131 cases of CHD) met the inclusion criteria for the analysis. Meta‐analysis indicated an incremental yield of 7.0% (95% CI, 5.3–8.6%) for the detection of CNVs using aCGH, excluding aneuploidy and 22q11 microdeletion cases. Subgroup results showed a 3.4% (95% CI, 0.3–6.6%) incremental yield in isolated CHD cases, and 9.3% (95% CI,   6.6–12%) when extracardiac malformations were present. Overall, an incremental yield of 12% (95% CI, 7.6–16%) was found when 22q11 deletion cases were included. There was an additional yield of 3.4% (95% CI, 2.1–4.6%) for detecting variants of unknown significance (VOUS). Conclusions: In this review we provide an overview of published data and discuss the benefits and limitations of using aCGH. If karyotyping and 22q11 microdeletion analysis by FISH are normal, using aCGH has additional value, detecting pathogenic CNVs in 7.0% of prenatally diagnosed CHD, with a 3.4% additional yield of detecting VOUS. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.